PROPERTIES OF CEMENT MORTARS REINFORCED WITH POLYPROPYLENE FIBERS - Oktay, Didem; Aktuerk, Buesra; Kabay, Nihat (YILDIZ TECHNICAL UNIV, 2014)
In this paper, the effect of polypropylene fibers (PF) on fresh and hardened properties of cement mortars produced with white cement is reported. Nine mixtures were prepared by using different volume fractions and different sizes of PF from 0 to 1.5% and 6 and 12 mm, respectively. Water to cement and sand to cement ratio by weight was kept constant as 0.4 and 3.0, respectively. PF with different length and amounts was introduced to mixtures and its effect on workability, density, water absorption, compressive strength, flexural strength and drying shrinkage were determined. Pore ratio at the cross-section of the specimens was calculated by image analysis. Test results showed that the addition of PF in higher amounts decreased workability, fresh and hardened density, compressive and flexural strength and increased water absorption and pore ratio of the mixtures. However when used in lower amounts, PF improved drying shrinkage and flexural strength.
Keywords: Polypropylene fiber; mechanical properties; workability; drying shrinkage; pore ratio; Engineering